THE EFFECTIVENESS OF DEVELOPING STUDENT WORKSHEETS BASED ON CAT TO IMPROVE THE STUDENTS’ ABILITY TO COMPREHEND MATHEMATIC AT GRADE VI SD METHODIST-12 MEDAN - Patri Janson Silaban; Asnita Hasibuan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
The ability to comprehend mathematic can be trained and improved in each student. Students Worksheet (LKPD) refers to a learning aid in the learning process. CAT (Computer Assisted Test) is one of the learning media designed to develop interactive LKPD. The method of this research method was Research and Development. Based on the evaluation from material experts in the field of mathematics education, it was obtained that the result for content feasibility, presentation, language, and graphics was 88.02% (Very Good).Moreover, the result of evaluation from the media experts revealed the percentage for aspects of media feasibility, content feasibility, presentation, and graphics was 90.73% (Very Good). Then, the media experts stated that the percentage of aspects of media feasibility, content feasibility, and presentation was 95.00% (very good). In addition, the results of individual test for the students’ responses showed that the aspects of content, objectives, feasibility, technical quality, and attractiveness was 92.00% (Very Good). The results of the individual test for students’ responses found that the percentage for aspects of learning content, objectives, feasibility, technical quality and attractiveness was 92.00% (Very Good). Then, the results of field test for the students' responses obtained that the percentage of aspects of content, objectives, technical quality, and attractiveness was 94.77% (Very Good). Finally, the results of the data analysis of the individual test for students’ responses obtained that the percentage of aspects of content, objectives, feasibility, quality and attractiveness was 92.00% (Very Good).